PENGEMBANGAN EKONOMI KREATIF SEBAGAI PARADIPLOMASI KOTA METROPOLITAN SEOUL - Gilang Nur Alam; Rizka Maharani; RMT Nurhasan Affandi; Windy Dermawan (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
Seoul Metropolitan City is one of the metropolitan cities in South Korea, which able to perceive its interest with self-government in international activities. Seoul Metropolitan City government has implemented paradiplomacy to develop its creative economy which is limited to aspects of music, drama, and fashion. This article uses qualitative methods with literature studies to support the required data. This article also seeks to describe the paradiplomacy carried out by the Seoul Metropolitan City government with self-government in a unitary state with a literature review covering transgovernmentalism, foreign relations, paradiplomacy, and creative economy. Besides, the authors also argue that the Seoul Metropolitan City government could optimize its potential with policies or actions taken by the Seoul Metropolitan City government on the aspects of music, drama, and fashion towards the global public.